Pengembangan Media PUZFOAM (Puzzle Styrofoam) untuk Meningkatkan Pemahaman Siswa pada Materi Struktur Tumbuhan - Savitri, Meta Winda Nur; Primasatya, Nurita; Wahyudi, Wahyudi (Efektor, 2022)
Abstract Out of the observation, it was found that teachers tend to use books as a guide in delivering material. When delivering material, the teacher did not do practicum. As a result, students are less interested in the material being taught because they do not understand the function of plant parts. This study aims to determine the method of how to make media, validity, practicaly, and effectiveness of the media. This study used research and development methods or R & D with ADDIE model. The results of the research on media development and students abilities are as follows: 1) At the media validation stage, Puzfoam Media (Puzzle Styrofoam) gets a cumulative score of 88.8 very valid information. 2) At the material validation stage, the material questionnaire for plant structure and its functions and the question questionnaire obtained score of 87.5 and 83. The information was very valid so it did not require revision, but there were notes. 3) Based on the data on the results of the media effectiveness test through evaluation questions, the cumulative results of all subjects got 91 results, which means the media effectiveness test is complete. 4) Based on the data from the practicality test of the media through the teacher's practicality questionnaire, the cumulative results of all scores get 90, which means the practicality test of this media is complete and very practical. 5) Based on the results of the students’ response questionnaire, a score of 89 (very valid) was obtained which was a very satisfying result.